Relación entre las Fugas de Agua y Consumos de Agua Potable en el Sector Residencial - Unach (2019)
The basic work of the entities that supply water consists of providing the liquid in quantity and quality necessary to compensate the needs of the consumers. Therefore, to maximize the physical efficiency of the systems, it is minimizing water losses due to leaks that can occur within the residential sector. Knowing how leaks influence the consumption of drinking water and sanitary appliances will help us find the present problems and also allow us to propose strategies to reduce the leaks that can occur within it. The main objective of this research was to determine the relationship between water leaks and consumption of drinking water in the residential sector. Supported in the method of urban and socioeconomic characterization and determination of 4 population ranges, several variables were analyzed as percentages of intra-household leakage, per capita consumption and the total number of appliances by strata. Within the procedure we use, linear trends, coefficient of determination (R) and p-value, supported by descriptive statistics. The results of this investigation confirmed that the intradomiciliary leaks if it affects the consumption of water for large and small cities. In addition, intradomiciliary leaks are generated by the total number of sanitary devices in large cities.